Gastric ESD under Heparin Replacement at High-Risk Patients of Thromboembolism Is Technically Feasible but Has a High Risk of Delayed Bleeding: Osaka University ESD Study Group - Toshiyuki Yoshio; Tsutomu Nishida; Naoki Kawai; Kiyonori Yuguchi; Takuya Yamada; Takamasa Yabuta; Masato Komori; Shinjiro Yamaguchi; Shinji Kitamura; Hideki Iijima; Shusaku Tsutsui; Tomoki Michida; et al. (Gastroenterology Research and Practice)
Objectives. Heparin replacement (HR) is often performed in patients with a high risk of thrombosis undergoing endoscopic procedures. However, information about the influence of HR is scarce. The aim of this study is to assess the clinical impact of HR for gastric endoscopic submucosal dissection (ESD). Methods. This is a retrospective study comprising approximately 1310 consecutive gastric neoplasms in 1250 patients, who underwent ESD in 5 institutes. We assessed the clinical findings and outcomes of ESD under HR, compared to ESD without HR as control. Results. A total of 24 EGC lesions in 24 patients were treated by ESD under HR. In the HR group, the complete en-bloc resection rate was 100%. The delayed bleeding rate was, however, higher in the HR group than in the controls (38% versus 4.6%). The timing of bleeding in the HR group was significantly later than in controls. In the control group, 209 patients discontinued antithrombotic therapy during perioperative period, and their delayed bleeding rate was not different from those without antithrombotic therapy (5.7% versus. 4.4%). A thromboembolic event was encountered in 1 patient under HR after delayed bleeding. Conclusion. ESD under HR is technically feasible but has a high risk of delayed bleeding.